Quinoline‐Based p300 Histone Acetyltransferase Inhibitors with Pro‐apoptotic Activity in Human Leukemia U937 Cells. Issue 3 (6th February 2014) - Lenoci, Alessia; Tomassi, Stefano; Conte, Mariarosaria; Benedetti, Rosaria; Rodriguez, Veronica; Carradori, Simone; Secci, Daniela; Castellano, Sabrina; Sbardella, Gianluca; Filetici, Patrizia; Novellino, Ettore; Altucci, Lucia; et al.
Abstract Chemical manipulations performed on 2‐methyl‐3‐carbethoxyquinoline (1), a histone acetyltransferase inhibitor previously identified by our research group and active at the sub‐millimolar/millimolar level, led to compounds bearing higher alkyl groups at the C2‐quinoline or additional side chains at the C6‐quinoline positions. Such compounds displayed at least threefold improved inhibitory potency toward p300 protein lysine acetyltransferase activity; some of them decreased histone H3 and H4 acetylation levels in U937 cells and induced high degrees of apoptosis (three compounds >10‐fold higher than compound 1) after treatment of U937 cells.